Pengaruh Metode Murotal Terhadap Kemampuan Membaca Al Qur’an Yang Benar Pada Mahasiswa Mentoring Angkatan 2010 UNISBA - Suhana Suhana; Fisa Stefani S (SCHEMA (Journal of Psychological Research), 2011)
Teaching methods of reading Al-Quran which is applied in a mentoring program students in class EUnisbafar using the lecture method and a manual which makes students less attention In learning because they feel that methods so less attractive. This research aimed to explore alternative methods of learning in reading the Qur’an on the student, that is VCD Murotal with an audiovisual show presents the reading of the Qur’an slowly. In those impressions of letters I each word uttered one by one and the connected in accordance with existing legal literature to compose a word. The results show the average error in reading the Qur’an after being given a spectacle VCD Murotal smaller than before administration spectacle, in the sense of the influence of the velocity murotal VCD learn to read the Qur’an has resulted significant impact. So this method can be used as an alternative teaching of reading Qur’an correctly.